A case-control study of phosphodiesterase-5 inhibitor use and Alzheimer’s disease and related dementias among male and female patients aged 65 years and older supporting the need for a phase III clinical trial - Henry, David S.; Pellegrino, Richard G. (PLOS ONE, 2023)
Background Phosphodiesterase-5 inhibitors (PDE5i) have been evaluated as a novel treatment for Alzheimer’s disease and related dementias (ADRD), but two recent cohort studies have offered opposing conclusions. Methods We performed an unmatched case-control study using electronic medical records from a large healthcare system to evaluate the association of PDE5i use and ADRD in patients ≥65 years old. Results Odds of PDE5i exposure were 64.2%, 55.7%, and 54.0% lower in patients with ADRD than controls among populations with erectile dysfunction, benign prostatic hyperplasia, and pulmonary hypertension, respectively. We observed odds ratios less than unity among males and females and with exposure to the PDE5i sildenafil (Viagra®) and tadalafil (Cialis®). We also evaluated the odds of exposure to two other common treatments for pulmonary hypertension: endothelin receptor antagonists (ERA) and calcium channel blockers (CCB). The odds of ERA exposure were 63.2% lower, but the odds of CCB exposure were 30.7% higher, in patients with ADRD than controls among the population with pulmonary hypertension. Conclusions Our results reconcile the opposing conclusions from the previous observational studies and support further research into using PDE5i for prevention and treatment of ADRD.